The National Being: Some Thoughts on an Irish Polity - Russell, George William, 1867-1935 (Salt Lake City, UT : Project Gutenberg, 2005)
"The National Being: Some Thoughts on an Irish Polity" by George William Russell is a philosophical essay written in the early 20th century. The book examines the character and aspirations of the Irish State, discussing the interplay between the physical and spiritual aspects of national identity. Russell delves into the importance of self-governance and national ideals, urging a reflection on Irish character to forge a path toward a meaningful civilization. The opening of the work introduces the idea of a newly independent Ireland, framed as an "infant State" emerging amid global conflict. Russell likens this state to a child needing nurturing from its guardians to thrive against challenges such as sectarianism. He emphasizes the necessity for a dual focus on both the body and soul of the nation$1 (Bhighlighting characteristics that need to be fostered in Irish society. He sets the stage for a deeper examination of the influences behind Irish identity, urging readers to contemplate how Ireland can develop an original character that respects its historical roots while aspiring toward a cohesive and noble future. Through this introduction, Russell establishes a compelling plea for intellectual and moral development to lay the foundations of what he envisions as a united and thriving Irish nation. (This is an automatically generated summary.)s
Release date is 2005-05-01
Produced by Jake Jaqua, and David Widger
Keywords: Cooperation; Ireland -- Economic conditions; Ireland -- Politics and government